An organic-inorganic polyacrylamide-based surface imprinted quantum dots for the impedimetric and voltammetric detection of diazepam in saliva with smartphone readout - Adegoke, Oluwasesan; Oyinlola, Kayode; Adeniyi, Kayode Omotayo; Achadu, Ojodomo J; Yang, Zhugen; Daeid, Niamh Nic (Elsevier, 2025)
Diazepam (DZP) is a muscle-relaxing, anxiety-relieving sedative drug; nonetheless, it is also an addictive drug that may be abused. This work reports on the development of a novel electrochemical nanosensor for diazepam using SiO2-encapsulated-3-mercaptopropionic acid-capped AuZnCeSeS quantum dots (QDs) overcoated with a molecularly imprinted polymer (MIP) on screen-printed carbon electrodes (SPCEs). Electrochemical, spectroscopic and electron microscopic characterization of the nanomaterial and modified electrode surface was carried out and is reported herein. Specifically, electrochemical characterization of the QDs/SPCE using cyclic voltammetry (CV) revealed that the QDs exhibit a higher electrode surface area whilst electrochemical impedance spectroscopy (EIS) characterization demonstrated a lower charge transfer resistance (Rct). To fabricate the electrochemical nanosensor, firstly, alloyed AuZnCeSeS QDs were synthesized in the organic phase and thereafter capped with 3-mercaptopropionic acid (MPA) via a ligand exchange reaction. The MPA-AuZnCeSeS QDs were encapsulated in a SiO2 layer to form a SiO2-MPA AuZnCeSeS QDs system. The QDs were drop-casted onto SPCEs to form a SiO2-MPA AuZnCeSeS QDs/SPCE transducer interface. Organic based acrylamide, used as a functional monomer, was electropolymerized via CV on the QDs/SPCE in the presence of the diazepam template with ethylene glycol dimethacrylate as a crosslinker and 2,2′-azobis(2-methylpropionitrile) as an initiator. Under optimum experimental conditions, DZP was detected using EIS and square wave voltammetry (SWV). Using a portable potentiostat and a hand-held smartphone-based potentiostat, DZP was quantitatively detected in saliva using the MIP@QDs/SPCE with a limit of detection (LOD) of 2.3 μM and 2.7 μM, respectively. The LOD for DZP from SWV analysis was 1.0 μM.
Keywords: Analytical Chemistry